2019
DOI: 10.1177/0961203319860198
|View full text |Cite
|
Sign up to set email alerts
|

The majority of Swedish systemic lupus erythematosus patients are still affected by irreversible organ impairment: factors related to damage accrual in two regional cohorts

Abstract: Background Although the survival of patients with systemic lupus erythematosus (SLE) has improved, irreversible organ damage remains a critical concern. We aimed to characterize damage accrual and its clinical associations and causes of death in Swedish patients. Methods Accumulation of damage was evaluated in 543 consecutively recruited and well-characterized cases during 1998−2017. The Systemic Lupus International Collaborating Clinics (SLICC)/American College of Rheumatology damage index (SDI) was used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 48 publications
7
15
0
Order By: Relevance
“…Second, our analysis assumed a constant rate of damage accrual throughout the follow‐up period and thus could not account for potential accelerations or decelerations in the average rate of change in SDI score over time. However, consistent with the results of previous studies conducted in a variety of different health care systems , we found a steady, linear rate of increase in mean SDI score during follow‐up, suggesting that our assumption about the constant rate of damage accrual among SLE patients is valid. Third, 277 patients (15.2% of the SLICC cohort) were excluded due to missing baseline or follow‐up data.…”
Section: Discussionsupporting
confidence: 91%
“…Second, our analysis assumed a constant rate of damage accrual throughout the follow‐up period and thus could not account for potential accelerations or decelerations in the average rate of change in SDI score over time. However, consistent with the results of previous studies conducted in a variety of different health care systems , we found a steady, linear rate of increase in mean SDI score during follow‐up, suggesting that our assumption about the constant rate of damage accrual among SLE patients is valid. Third, 277 patients (15.2% of the SLICC cohort) were excluded due to missing baseline or follow‐up data.…”
Section: Discussionsupporting
confidence: 91%
“…For example, in lupus nephritis (LN), nearly 10% of the patients progress towards end-stage kidney disease. Persistent disease activity, comorbidities and drug toxicity significantly contribute to the risk of progressive irreversible damage accrual and increased mortality [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite improved prognosis, the mortality rate stills exceeds that of the general population 4. Due to active inflammation, prolonged corticosteroid use, comorbidities and factors unrelated to SLE, organ damage accumulates in the majority of patients over time,1 5 6 with cardiovascular disease and renal failure being strong risk factors for premature mortality 4 7–9…”
Section: Introductionmentioning
confidence: 99%